Modification of character education into akhlaq education for the global community life - Imam Sutomo (IAIN Salatiga, 2014)
The term “character education” appears to be a massive movement aroundthe world as a concern to rise up a generation of children who have strongmoral character. All primary and secondary educational institutions socializecharacter education, including Indonesia since 2010. The Islamic world uses aspecific term “akhlaq education”. It has taken place throughout the history ofIslamic civilization and has succeeded in cultivating Muslim characters. Thecore of akhlaq education is in the spiritual purification and obedience to God.Research from various Islamic countries show that the model of akhlaq educationis not changed much. It is conserved from generation to generation, thatmake it far behind the sophistication of character education. Muslims seemnot to put up with adequate characters to mingle with the global society. Theimplementation of akhlaq education let students comprehend a peaceful lifeonly in their environment. Due to everyone’s use of the Western science andtechnology, Muslims also adapt to this phenomenon and take a benefit tofacilitate their needs. The format of character education as an instrument needsto be modified into akhlaq education, so that students are not locked into anarrow local insight and can take part in the life of the global community.This modification includes 1) adopting the content of character education for the global community, 2) providing insights for the role of teachers and educationalinstitutions, 3) variety of learning model, 4) involving parents andthe community, and 5) accommodating students from various religions.Istilah “pendidikan karakter” muncul menjadi gerakan masif di seluruh duniasebagai bentuk kepedulian untuk menyiapkan anak didik berkarakter baik.Semua lembaga pendidikan dasar dan menengah menyosialisasikan pendidikankarakter, termasuk Indonesia mulai tahun 2010. Dunia Islam menggunakanterm “pendidikan akhlaq” telah berlangsung sepanjang sejarah peradaban Islamdan telah berhasil dalam pembentukan karakter Muslim. Karakteristikpendidikan akhlaq terutama dalam penyucian rohani dan kepatuhan kepadaTuhan. Penelitian dari berbagai Negara Islam menunjukkan bahwa modelpendidikan akhlaq tidak banyak perubahan, konservasi dari generasi ke generasi,jauh tertinggal dengan kecanggihan pendidikan karakter. Anak didik Muslimtidak disiapkan dengan karakter yang memadai untuk masuk dalam kehidupanmasyarakat global. Seperti penggunaan ilmu dan teknologi Barat oleh semuaorang (termasuk Muslim), format pendidikan karakter sebagai instrumen perludiadaptasi dalam pendidikan akhlaq, agar anak didik tidak terbelenggu dalamwawasan lokal yang sempit dan dapat memasuki kehidupan masyarakat global.Adaptasi tersebut mencakup 1) content pendidikan karakter untukmasyarakat global, 2) wawasan guru dan peran lembaga pendidikan, 3) modelpembelajaran yang variatif, 4) pelibatan orang tua dan masyarakat, dan 5)menampung siswa lintas agama.